HEALTH INSURANCE LEGAL COUNSELING MIGRANT WORKERS IN PONOROGO - Arief Budiono; Absori Absori; Rika Maya; Syaifuddin Zuhdi; Moh Indra Bangsawan; Wafda Vivid Izziyana (Jurnal Abdimas Bina Bangsa, 2022)
Article 28 H paragraph (1) of the 1945 Constitution directly states that social security is the right of every human being. Article 34 paragraph (1) again mentions the constitutional basis for the need for a social security system. The next constitutional basis is Law Number 40 of 2004 concerning the National Social Security System. This background means that the state has a duty to build a comprehensive social security system and provide a wider sense of "security" for all Indonesian citizens, including migrant workers. Social security consists of National Health Insurance (JKN) and Employment Insurance.National Health Insurance is a concept of health protection adopted from various social protection concepts, namely protection efforts for the Indonesian people in general and migrant workers in particular to face vulnerability and illness which is equipped with strategies to obtain or protect health comprehensively. Health insurance for migrant workers can be interpreted as an effort from the state to help migrant workers by providing guarantees or protection for the health of migrant workers. Efforts to fulfill this have several important aspects related to the fulfillment of constitutional rights and legal protection in the context of implementing social security programs for migrant workers